Analisis Kelayakan Sosial Ekonomi Pengembangan Kampus II UIN Sunan Ampel di Kelurahan Gunung Anyar Kota Surabaya (EMARA: Indonesian Journal of Architecture, 2016)
The developments in higher education must be in line with the development of the world today, as the college itself is an institution with the function of reviewing, preserve, develop, and disseminate art, science and technology in order to educate the nation. The physical development of multicampus masterplan must have basic design principles as follows; flexibility, adaptability, orderliness, campus social life-oriented, formality and symbolizes the development of technology and culture of Indonesia in the future. This paper is part of the Campus Development Feasibility Study Report II UIN Sunan Ampel Surabaya in Gunung Anyar Surabaya. The social study is one of the substantial aspects in the preparation of a feasibility study toward land acquisition based on the public response againts the campus development plan. A descriptive qualitative method was use to collect and analyzed the data base on the result of communty feedback identification as well as the supporting secondary data. The analysis showed that the community strongly agree with the development plans in their surrounding areas as a means of education. The public has a positive image for the institution of UIN Sunan Ampel so they showed their enthusiasm with the campus development plan. The campus development are expected to contribute positively to community enhancement, both economic and social. However, it should be well anticipated the possibility of negative impacts that may occur as a result of the development plan, both socially as well as the physical condition of the environment.